Synergy between Civics and Social Sciences in Preventing Bullying Through Student Empathy and Tolerance - Dinar Ayu Mirunggan Sari; Rynaldi Setya Rachim; Nila Arzaqi (Journal of Pedagogi, 2025)
Bullying in schools remains a significant challenge in education due to its impact on students’ mental health and character development. This study aims to analyze how the synergy between Civics Education (PKN) and Social Studies (IPS) can foster students’ empathy and tolerance as an effort to prevent bullying. This research employed a qualitative case study approach, with data collected through observation, in-depth interviews, and documentation. The findings reveal that thematic and reflective integration of PKN and IPS encourages students’ social awareness and promotes active participation in building positive peer interactions. Teachers play a key role in connecting learning materials to students’ real-life experiences, enabling values of empathy and tolerance to be not only understood conceptually but also practiced in daily behavior. Moreover, a supportive, inclusive school environment strengthens the effectiveness of this approach. This study concludes that the synergy of PKN and IPS contributes meaningfully to character formation in preventing bullying at school.